Identification of Beach Carrying Capacity and Sedimentation-Based Nourishment Impacts at Ancol Beach Jakarta - I Ketut Antara; Willy Susanto; An Nuur Khairune Nisa; Fransisco Dei Graciano Gadu; Inti Pranawati; Gina Gartiwi PR (Jurnal Toursci, 2026)
Purpose. This study aims to analyze the carrying capacity of Ancol Beach, Jakarta, in relation to the sediment nourishment strategy as an effort to maintain the stability of coastal tourism areas. Method. The approach used is qualitative descriptive, using the literature study method, namely by collecting and analyzing secondary data from scientific journals, research reports, and related publications. The analysis was conducted by examining the five main dimensions of carrying capacity: Physical Carrying Capacity (PCC), Ecological Carrying Capacity (ECC), Social Carrying Capacity (SCC), Management Capacity (MCC), and Facility Carrying Capacity (FCC). Results. The findings in this study confirm that the interaction among the dimensions of carrying capacity is complex and that they affect one another. High dependence on meeting needs makes management quality a key factor in maintaining a balance between tourism utilization and environmental sustainability. Conclusion. An integrated, adaptive, and data-based management strategy is needed to ensure the sustainability of Ancol Beach as a coastal tourism destination.